Clinical characteristics and therapy response in unresectable melanoma patients stage IIIB-IIID with in-transit and satellite metastases - Zaremba, Anne; Philip, Manuel; Hassel, Jessica C.; Glutsch, Valerie; Fiocco, Zeno; Loquai, Carmen; Rafei-Shamsabadi, David; Gutzmer, Ralf; Utikal, Jochen; Haferkamp, Sebastian; Reinhardt, Lydia; Kähler, Katharina C.; et al. (European journal of cancer, 2021)
Introduction - Cutaneous melanoma is notorious for the development of in-transit metastases (ITM). For unknown biological reasons, ITM remain the leading tumour manifestation without progression to distant sites in some patients. - Methods - In total, 191 patients with initially unresectable stage III ITM and satellite metastases from 16 skin cancer centres were retrospectively evaluated for their tumour characteristics, survival and therapy response. Three groups according to disease kinetics (no distant progress, slow (>6 months) and fast (<6 months) distant progression) were analysed separately. - Results - Median follow-up time was 30.5 (range 0.8-154.0) months from unresectable ITM. Progression to stage IV was observed in 56.5% of cases. Patients without distant metastasis were more often female, older (>70 years) and presented as stage III with lymph node or ITM at initial diagnosis in 45.7% of cases. Melanoma located on the leg had a significantly better overall survival (OS) from time of initial diagnosis compared to non-leg localised primaries (hazard ratio [HR] = 0.61, 95% confidence interval [CI] 0.40-0.91; p = 0.017), but not from diagnosis of unresectable stage III (HR = 0.67, 95% CI 0.45-1.02; p = 0.06). Forty percent of patients received local therapy for satellite and ITM. Overall response rate (ORR) to all local first-line treatments was 38%; disease control rate (DCR) was 49%. In total, 72.3% of patients received systemic therapy for unresectable stage IIIB-D. ORR for targeted therapy (n = 19) was highest with 63.2% and DCR was 84.2% compared to an ORR of 31.4% and a DCR of 54.3% in PD-1 treated patients (n = 70). Patients receiving PD-1 and intralesional talimogene laherparepvec (n = 12) had an ORR of 41.7% and a DCR of 75%. - Conclusion - Patients with unresectable ITM and without distant progression are more often female, older, and have a primary on the leg. Response to PD-1 inhibitors in this cohort was lower than expected, but further investigation is required to elucidate the biology of ITM development and the interplay with the immune system.